PERANCANGAN SISTEM OTOMASI PEMANASAN MINYAK MENTAH PADA HEAT EXCHANGER PROSES PENGOLAHAN MINYAK MENTAH (STUDI KASUS UNIT KILANG PUSDIKLAT MIGAS CEPU) - WIBOWO, CHANDRA ARIF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of automation systems on crude oil distribution and heating components in the heat exchanger needs to be maximized. Based on this problem, the final project will design automation system for crude oil heating at the heat exchanger in Unit Kilang Pusdiklat Migas Cepu. The administration of the research set off from the analysis of operating data, design PFD and P&ID, selection and specification of sensor and actuator, making the control system architecture, design functional diagram, design of HMI display, and making program. The result of this research are design of PFD, P&ID, functional diagram which is based on standart documents from ISA-5.1-2009, selection the specification of sensor and actuator which is based on standart documents from ISA-20-1981 such as RTD, orifice plate, differential pressure transmitter, bimetal thermometer, and control valve. Design of automation system architecture on DCS Centum VP, design of HMI display which is based on standart documents from ISA-5.5-1985, and making program on DCS Centum VP.